Fear of Cancer Recurrence and Associated Factors Among Women with Female Cancer: A Cross-Sectional Study - Lovorka Brajković; Ivana Lozić; Dora Korać; Vanja Kopilaš (Healthcare, 2026)
Background/Objectives: The emotional impact of a cancer diagnosis may become particularly salient during survivorship, as survivors continue to face fears and concerns related to recurrence. Fear of cancer recurrence (FCR) is one of the most prevalent psychological challenges and significant unmet need among women with female cancer. The aim of this study was to assess the presence of FCR in predominantly breast cancer survivors, and to examine its relationship with certain demographic, clinical, and psychosocial factors. Methods: This cross-sectional study was conducted with a convenience sample of 120 women with a history of breast or gynecological cancer who were recruited over a two-month period through several cancer support associations across Croatia. Data were collected in person using a questionnaire comprising sociodemographic and clinical variables, as well as four self-reported instruments: the Fear of Cancer Recurrence Inventory–Short Form, Impact of Event Scale, Cancer Behavior Inventory–Brief Version, and Multidimensional Scale of Perceived Social Support. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient and hierarchical regression analysis. Results: In the final sample of 110 women, FCR levels were moderate, with 66.4% of participants reporting clinically significant levels. FCR was positively associated with chemotherapy (r = 0.22, p < 0.05), intrusive thoughts (r = 0.56, p < 0.01) and avoidance tendencies (r = 0.39, p < 0.01), and negatively associated with age (r = −0.26, p < 0.01) and self-efficacy for coping (r = −0.41, p < 0.01). In the final regression model, intrusive thoughts, coping self-efficacy, and chemotherapy were the only variables independently associated with fear of cancer recurrence. Conclusions: These findings indicate the presence of FCR in the period after primary treatment, particularly among breast cancer survivors, and highlight cognitive processing of cancer-related experiences and self-efficacy as potentially relevant areas for further research.